English Abbreviation Slang in the Online Pokemon Go Gaming Comunnity on Discord by Applying Speech Act Theory J.L Austin & John Searle - hafsa febinurrani; Andang Saehu; Erlan Aditya Ardiansyah (Journal of Educational Studies, 2026)
The rapid development of digital communication in online gaming relies heavily on abbreviation slang to convey meaning quickly and efficiently. On platforms like Discord, the accurate interpretation of this abbreviation  slang requires analyzing the surrounding context, as it functions as a strategic tool for user coordination rather than mere textual shortcuts. This study aims to identify English abbreviation slang within the online Pokémon Go Discord community and interpret its pragmatic functions using J.L. Austin and John Searle’s Speech Act Theory. Employing a descriptive qualitative method, data were collected through passive observation of active chat channels. The meanings of these abbreviation were then contextually interpreted and analyzed based on locutionary, illocutionary, and perlocutionary acts, along with Searle's illocutionary taxonomy. The interpretation of the findings reveals that abbreviation such as "LFG," "CP," and "AFK" operate as highly conventionalized speech acts, predominantly falling into the categories of Assertives, Expressives, and Directives. This abbreviation slang triggers cognitive, affective, and behavioral perlocutionary effects, facilitating shared understanding, emotional bonding, and concrete in-game actions. The study concludes that abbreviation slang in gaming communities transcends simple morphological truncation; its pragmatic interpretation demonstrates that these abbreviation are performative speech devices used to execute specific social and structural actions